THE ROLE OF INTERNATIONAL LAW IN PROTECTING AFGHAN ASYLUM SEEKERS AND AFGHAN REFUGEES IN IRAN - Mowahid, Ali Ahmad; Ahmadi, Fazl Ahmad (International Journal of Law in Changing World, 2025)
Iran, being a neighbouring and easily accessible country, has been the primary host of Afghan refugees for the last four decades. Although Afghan asylum seekers have been living in the country for a long time, they are provided with minimal human rights protection. This article examines international documents, laws, and regulations related to asylum seekers and refugees. It explores the status of asylum seekers and refugees in international law, focusing on Afghan asylum seekers in Iran. This research has been conducted using a descriptive-analytical method to the following research question: To what extent has international law and its related instruments been effective in enhancing protections and improving the situation of Afghan refugees in Iran? The findings reveal that, although international law has provided protective frameworks, it has not been able to compel Iran to respect the rights of Afghan asylum seekers. Domestic policies, economic conditions, and the lack of binding legal instruments have posed hindrances to effectively implementing these commitments. _____ EL PAPEL DEL DERECHO INTERNACIONAL EN LA PROTECCIÓN DE LOS SOLICITANTES DE ASILO Y REFUGIADOS AFGANOS EN IRÁN Irán, al ser un país vecino y de fácil acceso, ha sido el principal receptor de refugiados afganos durante las últimas cuatro décadas de la crisis afgana. Si bien los solicitantes de asilo afganos llevan mucho tiempo viviendo en el país, la protección de sus derechos humanos es mínima. Este artículo tiene como objetivo examinar documentos, leyes y normativas internacionales relacionados con los solicitantes de asilo y los refugiados, y explorar su situación en el derecho internacional, con especial atención a los solicitantes de asilo afganos en Irán. Esta investigación se ha realizado mediante un método descriptivo-analítico, y la pregunta de investigación se plantea de la siguiente manera: ¿En qué medida el derecho internacional y sus instrumentos relacionados han sido eficaces para mejorar la protección y la situación de los refugiados afganos en Irán? Los hallazgos del estudio revelan que, si bien el derecho internacional ha proporcionado marcos de protección, no ha logrado obligar a Irán a respetar los derechos de los solicitantes de asilo afganos. Las políticas internas, la situación económica en Irán y la falta de instrumentos jurídicos vinculantes han obstaculizado significativamente la implementación efectiva de estos compromisos. _____ 国际法在保护伊朗境内阿富汗寻求庇护者和阿富汗难民中的作用 伊朗作为邻国，交通便利，在过去四十年的阿富汗危机中一直是阿富汗难民的主要接收国。尽管阿富汗寻求庇护者在伊朗长期生活，但他们的人权保障却微乎其微。本文旨在考察与寻求庇护者和难民相关的国际文书、法律和法规，并探讨寻求庇护者和难民在国际法中的地位，特别关注伊朗境内的阿富汗寻求庇护者。本研究采用描述性分析方法，研究问题如下：国际法及其相关文书在多大程度上有效地加强了对伊朗境内阿富汗难民的保护并改善了他们的处境？研究结果表明，尽管国际法提供了保护框架，但却未能迫使伊朗尊重阿富汗寻求庇护者的权利。伊朗的国内政策、经济状况以及缺乏具有约束力的法律文书，对有效履行这些承诺构成了重大障碍。